The Entrepreneurial Practice Behavior of Chinese Group Business in Indonesia: Contextualization from Islamic Business Ethics - Arief, Suyoto; Ahmadi, Samsuddin Nur; Kamaluddin, Imam; Wibisono, Vina Fithriana (ITB AAS INDONESIA Surakarta, 2024)
The purpose of this study is to determine the entrepreneurial practice behavior (EPB) of Chinese groups in running and developing a business. These behaviors will be analyzed using the Islamic business ethics (IBE) perspective to contextualize Islamic values in entrepreneurial practice. This study uses the qualitative approach, and the data collection method uses triangulation such as observation, interview, and documentation. The research object was conducted in Ponorogo, East Java province, where are 67 shops managed by ethics. The result of this study showed that the EPB of Chinese group business ethics shows six (6) behaviors, is high motivation; learning business knowledge through formal and non-formal education; personal savings; commitment to settle all debts on time; fulfilling the rights of employees and costumers properly; and strong determination to develop a business innovation. Then, following contextualization from IBE, four (4) behaviors are al-Quwwah; al-Amanah; al-Hifdz; and al-‘Ilm. In addition, several things cannot be reconciled with Islamic roles there are, orientation business Islam; Islam obliges to study of religious knowledge through debt. Although some scholars allow it, Islamic principles recommend avoiding or at least limiting it as much as possible.